ECONOMIC APPROACHES TO ASSESSING THE EFFECTIVENESS OF COMPANIES’ INTELLECTUAL CAPITAL - Olga Evgenievna Ustinova (Science and Innovation Center Publishing House, 2018)
The issues of effective management of intellectual capital of economic entities in modern conditions become especially urgent and require detailed study. To this end, this article analyzes the main scientific approaches to understanding and evaluating effectiveness. Within the framework of the resource approach to the assessment of management effectiveness, a synergetic effect is identified, as a consequence of interaction and a combination of various factors and resources, including intellectual, material, financial, contributing to the growth of the basic economic indicators of the business entity. The results of the research in the future can be used to form a model for the economic evaluation of the influence of intellectual capital on the competitiveness of companies.